Foreword to the special section on molecular graphics and visual analysis of molecular data (MolVA 2021). (October 2021) - Byška, Jan; Krone, Michael; Sommer, Bjorn
Highlights: MolVA is the workshop on molecular graphics and visual analysis of molecular data. MolVA accepts papers addressing challenges in the visualization of molecular data. This special section contains the full papers presented at MolVA 2021. The topics include fabrication, uncertainty, topology analysis, and virtual reality. Graphical abstract: Image, graphical abstract